KEPEMIMPINAN TRANSFORMASIONAL KEPALA SMP - Edwar Edwar; Zakaria Zakaria; Osa Juarsa (UNIVERSITAS BENGKULU, 2017)
This research is aimed to describe the implementation of transformational leadership in Junior High School 4 of South Bengkulu. Especially, this research describes: (1) personnels’ comprehension and meaning on transformational leadership; (2) visions of principal’s transformational leadership; (3) implementation of aspects of transformational leadership; and (4) obstacles faced in the implementation of aspects of transformational leadership.The design/method of this research is descriptively qualitative. The subject are personels of Secondary/Junior High School 4 of South Bengkulu. The techniques of collecting the data in this research were used interviews, observations, and study of documents. The data was analyzed by elaborating data, displaying data, and making conclution. The results show that (1) personnels’ comprehension and meaning on transformational leadership is good and important; (2) visions of school principal are good and qualified; (3) the implementation of transformational leadership covers all four aspects (and all four aspects of transformational leadership were implemented in all six school administration aspects, namely budget, facilities, curriculum, students, personnels, and public relation; and (4) the obstacles faced in the implementation are non-technical and technical ones.